The Origins of Interventional Radiology as a Treatment of the Trauma Patient: A Personal Perspective - Sclafani, Salvatore J.A. (Seminars in Interventional Radiology, 2025)
The Trauma Radiology Service (TRS) at Kings County Hospital was founded in 1976 and immediately integrated into its trauma surgical service (TSS), one of the earliest trauma centers in the United States. For more than 35 years, the TRS introduced surgeons to many applications of advanced diagnostic imaging and interventional procedures that can be used in the care of the injured. Some of these are now standards of practice throughout the world. Arterial embolizations of critical vessels to the brain and viscera, the peripheral and central vasculature, and nonvascular procedures for complications of trauma were described, and indications and techniques were shared through key publications. An understanding of Dr. Ludwik Fleck's epistemology, with thought collectives, thought styles, and collective moods, helps explain the successful integration of interventional radiology in the trauma center.
Keywords: interventional radiology; trauma; embolization; bleeding